The chamberlains’ specializations and duties - Dr. Asma Farhan Abdel Rahman Al Sharab (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Chamberlain is one of the important positions that has emerged in the Islamic State. It is an administrative function set up to protect the caliph from murder and assassinations due to its frequent and proliferation in the Rashidi era and the attempt to assassinate Muawiya bin Abi Sufyan and Amr bin Al-Aas at the hands of the Kharijites and their success in assassinating the Caliph Ali bin Abi Talib, which made Muawiya bin Abi Sufyan seek to create a chamberlain job in the Islamic state, so she was interested Guarding the Caliph. Then he became standing at the Caliph’s door to arrange for the Caliph’s meetings, taking into account the social position of everyone who wanted to enter the Caliph, and the chamberlain function continued in later ages.